Assessment of Groundwater Quality, Heavy Metal Contamination, and Human Health Risks in Roundhill Municipal Landfill, Eastern Cape, South Africa - Timoti Silwani; Nomathemba Themba; Tlou Bernad Chokwe; Khomotso Semenya (Journal of Environmental Health and Sustainable Development, 2025)
Introduction: This study evaluates the impact of the Roundhill municipal landfill on groundwater quality in Berlin, Eastern Cape, South Africa. The objective was to assess physicochemical and microbial contamination, identify health risks, and trace pollution sources linked to landfill leachate. Materials and Methods: Groundwater samples were collected from five boreholes and one landfill leachate point. These were analysed for pH, total dissolved solids (TDS), conductivity, selected heavy metals (Al, Cd, Cr, Fe, Pb, Hg, Zn), and microbial contaminants (E. coli, Total Coliforms). Results were benchmarked against South African National Standard (SANS) 241 and World Health Organization (WHO) guidelines. Water Quality Index (WQI), Irrigation Water Quality Index (IWQI), and Human Health Risk Assessment (HHRA) models were applied. Pearson correlation and Principal Component Analysis (PCA) were used for statistical evaluation. Results: Significant contamination was observed in boreholes nearest the landfill (BH1 and BH2). Moreover, Cadmium (Cd) (569 µg/L), lead (Pb) (489 µg/L), and chromium (Cr) (451 µg/L) exceeded permissible limits and E. coli concentrations in BH2 reached 12,000 MPN/100 mL. WQI values exceeded 300, indicating water unsuitability for drinking. IWQI revealed potential soil permeability risks. HHRA showed Hazard Quotients >1 and elevated lifetime cancer risks, particularly for children. PCA and correlation analysis implicated landfill leachate as the main contamination source. Conclusion: The Roundhill landfill poses a serious threat to local groundwater quality and public health. Immediate mitigation measures—such as enhanced landfill containment, water treatment systems, routine monitoring, and regulatory enforcement—are necessary to prevent further environmental and health degradation.